Undertreatment or Overtreatment With Statins: Where Are We? - García-Fernández-Bravo, Irene; Torres-Do-Rego, Ana; López-Farré, Antonio; Galeano-Valle, Francisco; Demelo-Rodriguez, Pablo; Alvarez-Sala-Walther, Luis A. (Frontiers in Cardiovascular Medicine, 2022)
Statins, in addition to healthy lifestyle interventions, are the cornerstone of lipid-lowering therapy. Other low-density lipoprotein (LDL)-lowering drugs include ezetimibe, bile acid sequestrants, and PCSK9 inhibitors. As new evidence emerges from new clinical trials, therapeutic goals change, leading to renewed clinical guidelines. Nowadays, LDL goals are getting lower, leading to the “lower is better” paradigm in LDL-cholesterol (LDL-C) management. Several observational studies have shown that LDL-C control in real life is suboptimal in both primary and secondary preventions. It is critical to enhance the adherence to guideline recommendations through shared decision-making between clinicians and patients, with patient engagement in selecting interventions based on individual values, preferences, and associated conditions and comorbidities. This narrative review summarizes the evidence regarding the benefits of lipid-lowering drugs in reducing cardiovascular events, the pleiotropic effect of statins, real-world data on overtreatment and undertreatment of lipid-lowering therapies, and the changing LDL-C in targets in the clinical guidelines of dyslipidemias over the years.